The Effect of Square Finned Conformal Cooling (SFCC) on Cycle Time for Plastic Injection Moulding / K. Kamarudin ...[et al.] - Kamarudin, K.; Wahab, M.S; Ibrahim, M.; M. Batcha, M.F; A. Raus, A.; Ahmed, Aqeel; Sa'ude, N. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Cooling system is a significant factor in productivity and quality in the plastic injection moulding process. Numerous researchers demonstrated that conformal cooling channel yields significant improvement of productivity and quality of plastic injection moulding process. Apart from that, the advancement of Solid Free Form Technology (SFF) allows a mould designer to design a variety of conformal cooling channel geometry rather than conventional designs. This paper presents the research work to enhance the efficiency of square shaped groove conformal cooling channels which uses fins concept. Existing conformal cooling channel design that uses square shape groove was improved by incorporating fins to meet the best design that can reduce the cooling time. The effect of Square Finned Conformal Cooling (SFCC) design on cooling time was investigated by using Autodesk Moldflow Insight software. The simulation results indicated that different number of fins influences the cooling time. From the analysis, it was found that time to reach the ejection temperature was reduced by 19.4% for the cooling channels with 4 fins compared to existing cooling channel.